Effect of functional groups on physicochemical and mechanical behavior of biocompatible macroporous hydrogels - Rivero, Rebeca Edith (2015)
The increasing interest in studying the properties of biocompatible hydrogels is due to their possible applications in bioengineering. Properties of hydrogels based on N-isopropylacrylamide (NIPAM) and the effect caused by copolymerization with 2-acrylamido-2-methylpropanesulfonic acid (AMPS) or N-acryloyl-tris-(hydroxymethyl)aminomethane (HMA) were investigated. Hydrogels were synthesized by free radical polymerization at room temperature or by cryogelation at - 18°C. The presence of different functional groups (isopropyl, - SO3-, and -OH) and thermal conditions of polymerization affected the morphology and physicochemical and mechanical properties of hydrogels. Scanning electron microscopy (SEM) revealed the presence of macropores created by cryogelation with the morphology of the pores dependent on chemical composition of the copolymer. Poly(NIPAM-co-HMA) has spherical and isolated pores, whereas PNIPAM and Poly(NIPAM-co-AMPS) showed ellipsoidal interconnected pores. Three different water states were detected by differential scanning calorimetry (DSC), indicating the presence of nano- and macropores. Elastic modulus (E) was measured to be around 3-6.5 kPa by uniaxial compression. However, higher E values (20-30 kPa) and an anisotropic mechanical response were observed for PNIPAM and PNIPAM-co-AMPS hydrogels with ellipsoidal pores, a behavior that is almost similar to that of cartilage and bone tissues. Cytocompatibility studies using bovine fibroblasts (BFs) indicated good cell attachment and proliferation on PNIPAM-based hydrogel surfaces, although initially the cell adhesion varied depending on the composition of the surface. These hydrogels could be an interesting choice for the development of scaffolds in tissue engineering.